SOCIALIZATION OF DIGITAL LITERACY EDUCATION TO ANTICIPATE HOAX NEWS - Dessy Harisanty; Dyah Puspitasari Srirahayu; Nove Eka Variant Anna; Endang Fitriyah Mannan; Esti Putri Anugrah; Muhammad Rifky Nurpratama; Nasa Zata Dina (Darmabakti Cendekia: Journal of Community Service and Engagements, 2021)
Background: In the midst of the Covid-19 pandemic situation, hoax news emerged which often caused people to panic and make wrong decisions. The emergence of this hoax is because many people are not literate with information, so they trust all the information that is circulating. People also do not have social awareness to filter the information they get. Objective: This article aims to present the results of the socialization of digital literacy education to anticipate hoax news. Method: The method used in this community service is to provide socialization on the dangers of hoaxes and literacy education digital to anticipate hoax news, then explain how to search for valid and accurate information. Results: The result of this community service activity was an increase in public understanding of how to find valid and accurate Covid-19 information / news. As well as people's understanding of how to differentiate between true and false information about Covid-19. Conclusion: This community service activity has a positive impact on increasing public understanding of the spread of Covid-19 news on the internet.